All for Love; Or, The World Well Lost: A Tragedy - Dryden, John, 1631-1700 (Salt Lake City, UT : Project Gutenberg, 2000)
"All for Love; Or, The World Well Lost: A Tragedy" by John Dryden is a heroic drama written in 1677. Set in Alexandria, this blank verse tragedy focuses on the final hours of Marc Antony and Cleopatra's doomed relationship. As war looms and loyalties clash, Antony must choose between his passionate love for Egypt's queen and his duty to Rome, his wife Octavia, and his children. Misunderstandings, jealousy, and political intrigue spiral toward a devastating conclusion in this reimagining of Shakespeare's famous tale. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/All_for_Love_(play)
Release date is 2000-02-01
Produced by Gary R. Young
Keywords: Generals -- Rome -- Drama; Queens -- Egypt -- Drama; Antonius, Marcus, 83 B.C.?-30 B.C. -- Drama; Cleopatra, Queen of Egypt, -30 B.C. -- Drama; Tragedies (Drama); Romans -- Egypt -- Drama; Egypt -- History -- 332-30 B.C. -- Drama